2018
DOI: 10.1111/trf.14527
|View full text |Cite
|
Sign up to set email alerts
|

Association of killer cell immunoglobulin‐like receptors with spontaneous clearance of hepatitis C virus in the Chinese population

Abstract: In this study we identified KIR2DL5A-/2DL5B+ associated with HCV spontaneous clearance, while KIR2DL3/2DL3, 2DL3/2DL3+HLA-C1, or C1C1 associated with chronic infection. Our study highlighted the fact that the roles of KIR and KIR-HLA contributed to the control of HCV infection by innate immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…These findings are consistent with previous reports of KIR and HLA genotyping, indicating that the absence of HLA ligands for inhibitory KIRs could be associated with a significant reduction of CMV infection [11]. The cumulative evidence shows that KIR2DL2 –HLA-C1 and KIR2DL3 may be molecular biomarkers of virus-induced diseases [22,23,24].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with previous reports of KIR and HLA genotyping, indicating that the absence of HLA ligands for inhibitory KIRs could be associated with a significant reduction of CMV infection [11]. The cumulative evidence shows that KIR2DL2 –HLA-C1 and KIR2DL3 may be molecular biomarkers of virus-induced diseases [22,23,24].…”
Section: Discussionsupporting
confidence: 91%
“…As CF is accompanied by severe infectious lesions of the upper respiratory tract, the treatment of which is far from always effective, it cannot be ruled out, that the genetically induced weakness of the activating receptor site of natural killer cells is affecting this process. It should be noted, that we did not meet such studies in the literature, but based on literary data, which relate mainly to HIV infection [23][24][25] and hepatitis C [26][27][28][29][30], it can be concluded, that the more gentle progression of the disease correlates with increased activation of the functional activity of NK cells.…”
Section: Resultsmentioning
confidence: 89%
“…KIR2DL5A is an inhibitory receptor of immune response [33] and it is involved in immune response to viral infection and prognosis of certain malignant diseases. Shan et al reported that patients with KIR2DL5A -/2DL5B + genotype had increased HCV clearance [34]. In colorectal cancer, the presence of KIR2DL5A is related to increased complete response rate in patients treated with FOLFIRI chemotherapy [35], and KIR2DL5A is also a protective factor against breast cancer [36], while in pediatric leukemia patients after hematopoietic stem cell transplantation, the presence of KIR2DL5A is associated with higher relapse rate [37].…”
Section: Database Analysismentioning
confidence: 99%